Importance of COVID-19 in stomatological attention - Funes-Rumiche, Italo (2022)
The COVID-19 pandemic represents a challenge for health services and has produced a collapse of the same in many parts of the world and the dental surgeon has not been on the sidelines of this situation and has played an important role, producing a series of changes and reinforcing others, such as biosafety measures, for safe dental care. In the following review of the literature, the preponderance of the oral cavity in the COVID-19 disease is shown both in infectivity and severity in the presentation of symptoms, as well as the risk of the work performed by the surgeon dentist and how our profession can help mitigate contagions through the reduction of viral load with the use of certain products have a solid scientific basis with research carried out to demonstrate this action.